2017
DOI: 10.1101/106021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mindfulness and dynamic functional neural connectivity in children and adolescents

Abstract: Background: Mindfulness is a non-judgmental, present-centered awareness and acceptance of

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Compared to low trait mindfulness individuals, high trait mindfulness individuals show a higher level of transitions between brain dFC states and spend more time in one dFC state associated with task-readiness (Lim et al, 2018). Marusak et al similarly found that dFC (but not sFC) is related to mindfulness in youths such that more mindful youths have a higher level of transitions between dFC states (Marusak et al, 2018). Additionally, Cabral et al (Cabral et al, 2017) report a relationship between cognitive performance in older adults and slow switching between dFC states.…”
Section: Dynamic Functional Connectivity (Time-varying Functional Patmentioning
confidence: 99%
“…Compared to low trait mindfulness individuals, high trait mindfulness individuals show a higher level of transitions between brain dFC states and spend more time in one dFC state associated with task-readiness (Lim et al, 2018). Marusak et al similarly found that dFC (but not sFC) is related to mindfulness in youths such that more mindful youths have a higher level of transitions between dFC states (Marusak et al, 2018). Additionally, Cabral et al (Cabral et al, 2017) report a relationship between cognitive performance in older adults and slow switching between dFC states.…”
Section: Dynamic Functional Connectivity (Time-varying Functional Patmentioning
confidence: 99%
“…In exploratory analysis, we found that change in PVT performance across state was correlated with the change in the percentage of state transitions during resting-state scans. We have previously proposed a link between state transitions and the ability of the brain to refocus attention , which may represent a marker of cognitive flexibility (Li et al 2017, Marusak et al 2018; this theory is supported by data in macaques showing that sedation is associated with a loss of the rich repertoire of states seen in wakefulness (Barttfeld et al 2015). The negative effects of sleep deprivation on cognitive flexibility are well known (Harrison andHorne 1999, Durmer andDinges 2005), with increasing sleep pressure interfering with top-down executive function maintained by the prefrontal cortex (PFC).…”
Section: Decrease In State Transitions After Sleep Deprivation Are Almentioning
confidence: 99%
“…In our analyses, we formulated the temporal variability measure (equation 3) of each node in the dynamic FCN to capture the deviations of the node's role at each time from the static network. This measure is motivated by earlier studies that report measurable differences between static FCN and snapshots of the dynamic FCNAllen et al (2012); Marusak et al (2017Marusak et al ( , 2018. Moreover, any network level change can potentially influence how a node interacts with the rest of the network.…”
Section: Discussionmentioning
confidence: 99%